Equity Crowdfunding: The Secondary Market’s Implementation and Legal Protection for Investors Using Technology-Based Crowdfunding - Hanifiansyah Ilham Nugroho (Pancasila and Law Review, 2023)
The secondary market in equity crowdfunding aims to facilitate trading of Micro, Small, and Medium Enterprises (MSMEs) shares among investors, providing both exit and entrance strategies. For effective operation, these shares must be liquid, and the secondary market must operate fairly, orderly, and efficiently. Despite the introduction of the secondary market in Indonesia by the Financial Services Authority (OJK) in 2018, there remains significant room for evaluation and improvement. This thesis first examines the current organization of the secondary market in Indonesia, noting the lack of legal certainty for both organizers and users. It then explores regulatory frameworks for secondary markets in equity-based crowdfunding in the United States, which may inform the development of legal regulations in Indonesia, including the prohibition of share sales within the first year and the classification of equity-based crowdfunding for startups and medium-sized enterprises. Furthermore, applying American legal principles to the Indonesian context could enhance financial stability for issuing companies and reduce investor bankruptcy risks. The research highlights that the management and operational philosophy of the secondary market in equity crowdfunding should not be equated with that of traditional stock exchanges. Preventive legal protection for investors could be strengthened through OJK-issued guidelines on auto-reject limits, standardized trading mechanisms, trading hours, transaction fees, transparency in daily transaction summaries, and fair share price determination. Additionally, implementing criminal and administrative sanctions could provide further repressive legal protection.